2
$\begingroup$

Evaluate:
$$\sum_{n=0}^{\infty} \frac {(-1)^n}{4^{4n+1}(4n+1)} $$

I rewrote the sum as $$\sum_{n=0}^{\infty} \frac {1}{4^{8n-7}(8n-7)} - \sum_{n=0}^{\infty} \frac {1}{4^{8n-3}(8n-3)}$$
Now, I tried to express this as a Geometric Series and Partial Fraction but was unable to do so. I also tried to use Riemann Sum, but I don't know how to apply it here. Any help will be appreciated. Thanks!

$\endgroup$
6
$\begingroup$

Since the question is tagged "power-series", define $$f(x):=\sum_{n=0}^{+\infty}\frac{(-1)^nx^{4n+1}}{4^{4n+1}(4n+1)}.$$ We want to compute $f(1)$. Since $$f'(x)=\sum_{n=0}^{+\infty}\frac{(-1)^nx^{4n}}{4^{4n+1}}= \frac 14\sum_{n=0}^{+\infty}\left(\frac{-x^4}{4^4}\right)^n=\frac 14\frac 1{1+x^4/4^4}$$ and $f(0)=0$, we obtain that $$f(1)=\frac 14\int_0^1\frac{\mathrm{dx}}{1+\frac{x^4}{4^4}}.$$ This integral can be computed by noticing that for any $t$, $$t^4+1=(t^2-\sqrt 2 t+1)(t^2+\sqrt 2 t+1),$$ and doing a partial fraction decomposition.

$\endgroup$
  • $\begingroup$ How did you know to choose that function. Which concept is this? BTW excellent answer. $\endgroup$ – Henry Jun 8 '14 at 20:31
  • $\begingroup$ The series is almost geometric, but there is the term $4n+1$ on the denominator. It can be "cancelled" by differentiation of a power of $x$. $\endgroup$ – Davide Giraudo Jun 8 '14 at 20:34
  • $\begingroup$ OK, but what do you mean when you say 'since the question is tagged "power-series"'? I tagged power series because I thought it had something to do with G.P. $\endgroup$ – Henry Jun 8 '14 at 20:41
  • $\begingroup$ I introduced a function which is expressed as a power series. $\endgroup$ – Davide Giraudo Jun 8 '14 at 20:45
  • $\begingroup$ Mr Davide Giraudo, please see this link: The Easy Peasy Sum of Series. I have suspicion on this OP is taken from my question that I posted on Brilliant. $\endgroup$ – Anastasiya-Romanova 秀 Jun 10 '14 at 8:11
1
$\begingroup$

This is $f(1)$ where $$f(x) = \sum_{n=0}^\infty \dfrac{(-1)^n}{4^{4n+1} (4n+1)} x^{4n+1}$$ Note that $f(0) = 0$, and differentiate term-by-term to get $f'(x)$ as a geometric series. Then integrate.

$\endgroup$
1
$\begingroup$

Define $f(x) = \displaystyle\sum_{n = 0}^{\infty} \dfrac{(-1)^nx^{4n+1}}{4n+1}$. Notice that $f(\tfrac{1}{4}) = \displaystyle\sum_{n = 0}^{\infty} \dfrac{(-1)^n}{4^{4n+1}(4n+1)}$ is the sum in question.

It is easy to see that this power series converges for $|x| < 1$.

Thus, we can differentiate termwise to get $f'(x) = \displaystyle\sum_{n = 0}^{\infty} (-1)^nx^{4n} = \dfrac{1}{1+x^4}$ for all $|x| < 1$.

Clearly, $f(0) = 0$, Hence, $f(\tfrac{1}{4}) = f(\tfrac{1}{4}) - f(0) = \displaystyle\int_{0}^{\tfrac{1}{4}}f'(x)\,dx = \displaystyle\int_{0}^{\tfrac{1}{4}}\dfrac{1}{1+x^4}\,dx$

This integral can be evaluated using partial fractions, but it is messy.

$\endgroup$
1
$\begingroup$

The series for $\tanh^{-1}(x)$ and $\tan^{-1}(x)$ are \begin{align} \tanh^{-1}(x) &= \sum_{n=0}^{\infty} \frac{x^{2n+1}}{2n+1} \\ \tanh^{-1}(x) &= \sum_{n=0}^{\infty} \frac{(-1)^{n} \ x^{2n+1}}{2n+1}. \end{align} Adding the series together leads to \begin{align} \sum_{n=0}^{\infty} \frac{x^{4n+1}}{4n+1} &= \frac{1}{2} \left( \tanh^{-1}(x) + \tanh^{-1}(x) \right) \end{align} and upon setting $x = e^{i \pi/4}/4$ the resulting series is \begin{align} \sum_{n=0}^{\infty} \frac{(-1)^{n}}{4^{4n+1} \ (4n+1)} = \frac{1}{2} \left( \tanh^{-1}\left(\frac{e^{i \pi/4}}{4}\right) + \tan^{-1}\left(\frac{e^{i \pi/4}}{4}\right) \right). \end{align} After some reductions it can be shown that the series in question is given by \begin{align} \sum_{n=0}^{\infty} \frac{(-1)^{n}}{4^{4n+1} \ (4n+1)} &= \frac{1}{4\sqrt{2}} \left[ \ln\left(\frac{17+4\sqrt{2}}{17-4\sqrt{2}}\right) + 2 \tan^{-1}\left(\frac{4\sqrt{2}}{15}\right) \right]. \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.